ANALISIS KESALAHAN SISWA DALAM PEMECAHAN SOAL ASESMEN KOMPETENSI MINIMUM NUMERASI BERDASARKAN TEORI POLYA - Zeinul Arifin; Tuhfatul Janan (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2023)
Qualitative descriptive is the type of research applied to this study, with the aim of describing the types and what causes students to make mistakes in solving AKM numeracy questions. The test is in the form of AKM numeration questions with 6 students as subjects. The results showed that the students' biggest mistakes were made at the stage of implementing the plan with a percentage of 9.96%, the stage of making plans with a percentage of 7.62%, the stage of understanding the questions with a percentage of 7.23%, and 4.88% at the stage of re-examining the results. which is obtained. The cause of the error at the stage of understanding the questions was that students were not used to writing things that were known and asked about the questions, at the planning stage students were not used to writing down the steps for solving them and tended not to understand the questions so that they had difficulty drawing up plans. The cause of the error at the stage of carrying out the plan is the lack of focus on students in counting and writing digit numbers. The cause of the error at the stage of looking back at the results obtained is that students are not used to checking and making conclusions from answers.Keywords: student error, AKM numeration, Polya’s theory